2019
DOI: 10.3390/sports7070174
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to the Fatigue in Young Soccer Players Resulting from Sided Games

Abstract: It is crucial to understand the fatigue associated with sided games (SGs) of soccer in the training context, in order to establish the appropriate intervals between training sessions. Thus, the aim of this study was to investigate the effects of different SGs on internal load, measured by the session rating of perceived exertion (sRPE), and on sprint performance. Ten outfield players (age: 14.5 ± 0.5 years, height: 169 ± 6 cm, body mass: 59.7 ± 6.4 kg) belonging to U15 age category participated in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, our findings can be related to the fact that amateur and professional players' kinematic profiles in SSGs differ in the amount of high-intensity actions (Dellal et al, 2011). Additionally, no correlation was reported between changes in linear sprint performances and the rate of perceived exertion registered during the four different 5v5 SSG protocols (Castillo et al, 2019). It is also suggested that interindividual differences exist between the perceived effort and the lactate responses of players during SSGs (Köklü et al, 2015).…”
Section: Relationship Between Load Variables and Performance Changesmentioning
confidence: 55%
See 1 more Smart Citation
“…However, our findings can be related to the fact that amateur and professional players' kinematic profiles in SSGs differ in the amount of high-intensity actions (Dellal et al, 2011). Additionally, no correlation was reported between changes in linear sprint performances and the rate of perceived exertion registered during the four different 5v5 SSG protocols (Castillo et al, 2019). It is also suggested that interindividual differences exist between the perceived effort and the lactate responses of players during SSGs (Köklü et al, 2015).…”
Section: Relationship Between Load Variables and Performance Changesmentioning
confidence: 55%
“…A lower number of repetitions and longer resting periods compensate for players' neuromuscular performance decrement. This can also be achieved by reducing the pitch size of SSGs (Castillo et al, 2019). The question Frontiers in Physiology frontiersin.org remains whether declines in reactive agility and perceptual-cognitive performance can be compensated as well.…”
Section: Effects Of Ssg On Neuromuscular Performancementioning
confidence: 99%
“…In general, players at these early ages experience lower level of fatigue than their older teammates 29 . Some studies have demonstrated that the level of neuromuscular fatigue manifested by the loss of performance in the ability to accelerate or jump after SSCG cessation is increased in older adolescent and professional soccer players [21][22][23] . Thus, the impact of SSCGs on neuromuscular performance in young soccer players seems to be age-dependent, progressively increasing as players pass through adolescence and reach adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Younger players show distinct physical and technical-tactical responses to SSCGs compared to their older and more experienced teammates 19,20 . Furthermore, some investigations have revealed that SSCGs can induce a decrement in speed-power related abilities (e.g., 30 m sprint time and countermovement [CMJ] height) after different SSCG formats in soccer players [21][22][23] . However, the effects of SSCGs with varying pitch size and tactical rules on the neuromuscular abilities of young players in the early ages of adolescence (11-13 years) are less evident.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation